solve 3(x+2) +4(x-3) =6(2-5) +4
Answers
Answered by
3
Step-by-step explanation:
this is the answer of this question .....
please mark my answer as brainliest please....
Attachments:
![](https://hi-static.z-dn.net/files/dac/3b4ad31876542ce8562c953c94a46017.jpg)
Answered by
0
Answer:
-8/7
Step-by-step explanation:
3x+6+4x-12=-18+4
=7x=-14+6
x= -8/7.
hope it helps......
Similar questions
English,
3 months ago
Social Sciences,
3 months ago
Physics,
3 months ago
Science,
6 months ago
Social Sciences,
1 year ago